2010
DOI: 10.1016/j.alcohol.2009.09.033
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent ethanol exposure: does it produce long-lasting electrophysiological effects?

Abstract: This review discusses evidence for long lasting neurophysiological changes that may occur following exposure to ethanol during adolescent development in animal models. Adolescence is the time that most individuals first experience ethanol exposure and binge drinking is not uncommon during adolescence. If alcohol exposure is neurotoxic to the developing brain during adolescence, not unlike it is during fetal development, then understanding how ethanol affects the developing adolescent brain becomes a major publ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(47 citation statements)
references
References 143 publications
1
45
1
Order By: Relevance
“…Imaging and neurobiological research has shown that chronic alcohol consumption can lead to white matter degradation, disrupt neurocircuitry, and impact neural plasticity which can alter neurotransmission, particularly by increasing tonic inhibition (Cardenas et al, 2005;Crews et al, 2005;Herting et al, 2010;McBurney and Balaban, 2009;Oscar-Berman and Marinkovic, 2007;Pfefferbaum et al, 2010;Santhakumar et al, 2007;Sullivan and Pfefferbaum, 2005). Particularly relevant to the collegeaged population, high doses of adolescent ethanol exposure has been shown to produce lasting changes in functional brain activity (for review, see Ehlers and Criado, 2010). These changes are likely to reflect the neuroadaptational response to alcohol involving alterations in the healthy functional balance between inhibitory and excitatory mechanisms (Clapp et al, 2009;Fleming et al, 2009;Heiss et al, 2008;Higley and Contreras, 2006).…”
Section: Discussionmentioning
confidence: 98%
“…Imaging and neurobiological research has shown that chronic alcohol consumption can lead to white matter degradation, disrupt neurocircuitry, and impact neural plasticity which can alter neurotransmission, particularly by increasing tonic inhibition (Cardenas et al, 2005;Crews et al, 2005;Herting et al, 2010;McBurney and Balaban, 2009;Oscar-Berman and Marinkovic, 2007;Pfefferbaum et al, 2010;Santhakumar et al, 2007;Sullivan and Pfefferbaum, 2005). Particularly relevant to the collegeaged population, high doses of adolescent ethanol exposure has been shown to produce lasting changes in functional brain activity (for review, see Ehlers and Criado, 2010). These changes are likely to reflect the neuroadaptational response to alcohol involving alterations in the healthy functional balance between inhibitory and excitatory mechanisms (Clapp et al, 2009;Fleming et al, 2009;Heiss et al, 2008;Higley and Contreras, 2006).…”
Section: Discussionmentioning
confidence: 98%
“…Studies indicate that physiological changes in early adolescence are not limited to biological changes that mark the onset of puberty but also include brain growth and neural remodeling marked by synaptic cortical remodeling and changes in neurotransmitter receptors and transporters (e.g., Crews et al, 2007;Giedd, 2004;Nixon et al, 2010). During the period of brain remodeling, young people may be more vulnerable to harmful environmental shocks, including exposure to ethanol, that could lead to long-term problems, psychopathology, and priming of neurochemical pathways involved in drug metabolism (De Bellis et al, 2005;Ehlers and Criado, 2010;Volkow and Li, 2005;Witt, 2010).…”
Section: Sensitive-period Hypothesismentioning
confidence: 99%
“…Several studies of substance abuse have used qEEG in adolescent and young adult substance abusers. Ehlers and Criado (2010) electrophysiological effects produced by adolescent alcohol exposure. The animal model studies reviewed provide evidence that demonstrates that relatively brief exposure to high levels of ethanol during a period corresponding to parts of adolescence in the rat is sufficient to cause long-lasting changes in functional brain activity.…”
Section: Eeg and Erp In Sudmentioning
confidence: 99%